PENGARUH DUKUNGAN ORGANISASI, GAYA KEPEMIMPINAN, DAN KECERDASAN EMOSIONAL TERHADAP KINERJA KARYAWAN DINAS LINGKUNGAN HIDUP KOTA SURAKARTA - Kurniawati, Ely; Aji, Ambyah Atas (Widya Dharma Journal of Business - WIJoB, 2024)
In this study, the authors aimed to determine organizational support, leadership style, and emotional intelligence on the performance of employees of the Surakarta City Environmental Service. Organizational Support (X1), Leadership Style (X2), Emotional Intelligence (X3), Employee Performance (Y). This research is a quantitative case study. Primary data obtained by questionnaire method from a sample of 100 respondents. The analysis technique used is multiple linear regression test, T test, F test, and coefficient of determination test. The results of this study indicate that organizational support, leadership style, and emotional intelligence have a significant effect on the performance of employees of the Surakarta City Environmental Service both partially and simultaneously.